PEMBINAAN DAN PENDAMPINGAN KEPADA PENAMBANG EMAS TANPA IJIN DI DESA NOELTOKO, KEC.MIOMAFFO BARAT, KAB.TTU - Fani Serangmo; Herry Zadrak Kotta; Woro Sundari; Ika Krisnasiwi; Noni Banunaek; Yusuf Rumbino (LPPM UMRI, 2019)
Abstract Exploitation of natural resources through unlicensed gold mining (PETI) is not in accordance with mining operational standards occurring along the Noeltoko River, West Miomaffo Subdistrict, Timor Tengah Utara Regency, East Nusa Tenggara Province resulting in damage and environmental degradation. Changes and environmental damage include the formation of dug holes around the river flow, turbidity of water, changes in river flow. Other problems that arise are conflicts between these PETI workers and with other communities. This community service activity aims to provide an understanding to the community about the importance of maintaining and caring for rivers from excavation in the river walls that can cause debris / landslides explaining the impact of the use of hazardous materials such as mercury / mercury and cyanide, socialization of regulations regarding the formation of People's Mining Areas (WPR) ), introducing